AN UNUSUAL CASE OF CHROMOBLASTOMYCOSIS DUE TO FONSECAEA PEDROSOI IN SOUTH KERALA FOLLOWING A LEECH BITE: A CASE REPORT - Ashna Ajimsha; Neeraja C. K.; Kiran Subhash (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Chromoblastomycosis is a chronic cutaneous and subcutaneous fungal infection caused by melanized or brown-pigmented fungi, most commonly Fonsecaea pedrosoi. Purpose: This case report describes an unusual instance of chromoblastomycosis caused by F. pedrosoi in a woman from South Kerala with a preceding history of a leech bite, highlighting the importance of combining clinical examination, histopathology, fungal culture, and molecular sequencing for accurate diagnosis and effective management of this rare and chronic fungal infection. Case: A 54-year-old housewife presented with a 3 × 2 cm erythematous plaque on the dorsal aspect of left hand at the site of anatomical snuffbox. She reported a history of leech bite four years back at the same site. Dark pigmented colonies were isolated on Sabouraud dextrose agar. Skin biopsy for histological analysis, revealed sclerotic bodies, and Sanger sequencing. The patient was treated with oral itraconazole for two months. Result: The diagnosis of chromoblastomycosis was confirmed through fungal culture, histopathological examination revealing sclerotic bodies, and Sanger sequencing identifying F. pedrosoi. The patient responded well to two months of oral itraconazole over two months, with no recurrence of lesions noted on follow-up. Conclusion: Accurate identification of chromoblastomycosis is crucial due to its resistance to treatment and varied clinical manifestations, which often lead to misdiagnosis. However, combining systemic antifungal therapy with physical and surgical modalities has been shown to improve outcomes such an atypical mode of transmission underscores the need for heightened clinical awareness, especially in endemic areas or among patients with unusual environmental exposures.